Preparation of porous adsorbent via Pickering emulsion template for water treatment: A review - Zhu, Yongfeng; Wang, Wenbo; Yu, Hui; Wang, Aiqin (Journal of environmental sciences (China), 2020)
Porous materials as emerging potential adsorbents have received much more attention because they are capable of capturing various pollutants with fast adsorption rate, high adsorption capacity, good selectivity and excellent reusability. In order to prepare porous materials with decent porous structure, Pickering emulsion template method has been proved to be one of the most effective technologies to create pore structure. This paper reviewed comprehensively the latest research progress on the preparation of porous materials from various Pickering emulsions and their applications in the decontamination of pollutants (e.g., heavy metal ions, organic pollutants) and in the oil/water separation. It was expected that the summaries and discussions in this review will provide insights into the design and fabrication of new efficient porous adsorbents, and also give us a better understanding of the subject. [Display omitted]